ELEFAN-based population dynamics of yellowlined goatfish Upenaeus sulphureus from the Bay of Bengal - Mustafa, MD Golam (Indian Journal of Fisheries, 2011)
Upellaeus sulphureus is the most abundatilamong the goatfish species available inthe northern Bay of Bengal of Bangladesh.This species usually moves in schooL It formsa considerable part of the demersal fishery andaccounts for 3Â°/.) of the total biomass.